Sodium-ion battery negative electrode material and preparation method thereof, sodium-ion battery and power-related equipment
By using sodium alkylsulfonate and sodium alkyl as a template agent, combined with water thermal reactions and roasting methods, the sodium ion battery negative material of the porous spherical hard carbon structure is prepared to solve the low efficiency and high cost of hard carbon materials and high costs. The problem significantly improves the performance and reversibility of the battery.
Patent Information
- Application Number
- CN202411499134.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low initial Coulombic efficiency and high cost of hard carbon materials in sodium ion batteries limit their practical application.
The use of sodium alkylsulfonate and sodium alkyl as a template agent, the negative electrode material of the sodium ion battery is prepared by water thermal reactions and roasting methods, and carbon nanotubes are used to form a porous spherical hard carbon structure.
Improve the transmission efficiency, circulation life and rapid charging of the sodium ion battery, reduce the cost of the material, and improve the percentage performance.
Smart Images

Figure CN119370828A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a negative electrode material for sodium ion batteries and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] The scarcity and uneven distribution of lithium resources have increased costs, which has limited the application of lithium in large-scale energy storage. Sodium-ion batteries are rich in resources, low in cost, and have similar electrochemical properties to lithium-ion batteries. They can be used as a superior alternative to reasonably make up for the shortage of lithium-ion battery resources.
[0003] Among the negative electrode materials for sodium-ion batteries, hard carbons have great potential for practical application due to their large interlayer spacing, low operating voltage platform, and large capacity. However, the practical application of these hard carbons in sodium-ion batteries is still limited by two major obstacles, including low initial Coulombic efficiency and high cost due to low carbon yield or high cost of precursors.
[0004] Therefore, the development of low-cost, high-specific-capacity hard carbon is an urgent need to promote the application of sodium-ion batteries. Summary of the invention
[0005] The purpose of this application is to provide a sodium ion battery negative electrode material and a preparation method thereof, a sodium ion battery and electrical equipment to solve the above problems.
[0006] To achieve the above objectives, the present application provides a first aspect of a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0007] The organic acid, the organic amine and water are first mixed to obtain a solution A;
[0008] Sodium alkyl sulfonate, sodium alkyl olefinate and water are mixed for the second time to obtain solution B;
[0009] The solution A and the solution B are mixed for the third time to obtain a solution C;
[0010] The solution C and the carbon nanotubes are mixed for the fourth time to obtain a solution D;
[0011] The solution D is subjected to hydrothermal reaction and solid-liquid separation to obtain a composite precursor;
[0012] The composite precursor is calcined under a protective atmosphere to obtain a negative electrode material for a sodium ion battery.
[0013] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0014] A. the organic acid comprises citric acid;
[0015] B. the organic amine comprises octamethylenediamine;
[0016] C. the sodium alkyl sulfonate includes sodium dodecyl sulfonate;
[0017] D. the alkyl olefin sodium includes sodium hexadecene-9-olefin;
[0018] E. The specific surface area of the carbon nanotubes is ≥700 cm 2 / g;
[0019] The density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ;
[0020] F. The endpoint of the second mixing is that the solution B forms a Tyndall effect.
[0021] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0022] A. The mass ratio of the organic acid, the organic amine and the water is 0.4832-1:0.2885-1:100-200;
[0023] B. The mass ratio of the sodium alkyl sulfonate, the sodium alkyl olefinate, and the water is 0.054-1:0.022-1:60-100;
[0024] C. The mass ratio of the solution A to the solution B is 1.677-2:1-2;
[0025] D. The liquid-to-solid ratio of the solution C and the carbon nanotubes is 1L-2L:1.677g-2g.
[0026] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0027] A. before the hydrothermal reaction, the solution D and ethanol are mixed for the fifth time and ultrasonicated;
[0028] B. The temperature of the hydrothermal reaction is 160°C-240°C, and the time is 6h-8h;
[0029] C. The protective gas in the protective atmosphere includes one or more of argon, argon and nitrogen;
[0030] D. The calcination temperature is 1000°C-1400°C, the time is 2h-15h, and the heating rate is 5°C / min-10°C / min;
[0031] E. The stirring rate of the first mixing is 600r / min-800r / min, and the time is 2h-4h;
[0032] F. The stirring rate of the second mixing is 600r / min-800r / min, and the time is 2h-4h;
[0033] G. The third mixing comprises: adding the solution A dropwise into the solution B;
[0034] H. The stirring rate of the fourth mixing is 600r / min-800r / min, and the time is 2h-4h.
[0035] Optionally, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0036] A. The mass ratio of the solution D to the ethanol is 212.5-425:1-2;
[0037] B. The ultrasonic time is 1h-2h.
[0038] A second aspect of the present application provides a sodium ion battery negative electrode material, which is prepared by the preparation method of the sodium ion battery negative electrode material.
[0039] A third aspect of the present application provides a sodium ion battery, comprising the sodium ion battery negative electrode material and an electrolyte.
[0040] Optionally, the preparation method of the electrolyte includes:
[0041] Dimethyl ether, sodium trifluoromethanesulfonate and sodium methyl mercaptan are mixed.
[0042] Optionally, the mass ratio of the ethanol dimethyl ether, the sodium trifluoromethanesulfonate, and the sodium methyl mercaptan is 90-100:17.206-20:0.1-0.2.
[0043] A fourth aspect of the present application provides an electrical device, including the sodium ion battery.
[0044] Compared with the prior art, the beneficial effects of this application include:
[0045] The preparation method of the negative electrode material for a sodium ion battery provided in the present application adopts sodium alkyl sulfonate and sodium alkyl olefinate as template agents, and spherical micelles can be formed in the solution when the critical colloid point is reached, wherein carbon nanotubes are attachment points, and in an acidic environment, the organic amine decomposes and undergoes an aldol condensation reaction on the carbon nanotubes to form a carbon layer structure on the template micelles, and gradually forms a composite precursor under hydrothermal treatment, and in addition, the organic acid will react with the aldehyde substances produced by the decomposition of the amine substances by a weak acid-base reaction, further condense into a long-chain structure, provide a carbon source for the growth of the carbon balls, and then obtain the negative electrode material for a sodium ion battery after calcination.
[0046] The sodium ion battery negative electrode material provided by the present application comprises hard carbon formed by carbon nanotubes and multiple porous spherical hard carbons connected in series. The improvement of the porous structure and the surface interface is beneficial to the rapid transmission of electrons and the rapid diffusion of particles.
[0047] The sodium ion battery provided in the present application has enhanced transmission efficiency, cycle life, and reversibility during rapid charge and discharge, and exhibits excellent rate performance.
[0048] The electrical equipment provided by the present application greatly reduces the waiting time for charging, improves energy utilization efficiency, and thus also improves the utilization efficiency of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0050] Figure 1 This is a SEM image of the sodium ion battery negative electrode material provided in Example 1;
[0051] Figure 2 This is a graph showing the electrochemical performance of the sodium ion battery provided in Example 1. DETAILED DESCRIPTION
[0052] As used herein:
[0053] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0054] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0055] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0056] In these examples, parts and percentages are by mass unless otherwise indicated.
[0057] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0058] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0059] The first aspect of the present application provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0060] The organic acid, the organic amine and water are first mixed to obtain a solution A;
[0061] Sodium alkyl sulfonate, sodium alkyl olefinate and water are mixed for the second time to obtain solution B;
[0062] The solution A and the solution B are mixed for the third time to obtain a solution C;
[0063] The solution C and the carbon nanotubes are mixed for the fourth time to obtain a solution D;
[0064] The solution D is subjected to hydrothermal reaction and solid-liquid separation to obtain a composite precursor;
[0065] The composite precursor is calcined under a protective atmosphere to obtain a negative electrode material for a sodium ion battery.
[0066] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0067] A. the organic acid comprises citric acid;
[0068] In some embodiments, citric acid is weakly acidic, and the acidic environment formed can make the reaction more complete. In addition, citric acid is easy to react with aldehyde substances with weak acid-base reaction, further providing a carbon source.
[0069] B. the organic amine comprises octamethylenediamine;
[0070] In some embodiments, octamethylenediamine is a short-chain amine substance that decomposes under acidic conditions and high temperature and pressure. The intermediate product can produce aldehyde substances and undergo self-condensation reaction, thereby growing on the soft template.
[0071] C. the sodium alkyl sulfonate includes sodium dodecyl sulfonate;
[0072] D. the alkyl olefin sodium includes sodium hexadecene-9-olefin;
[0073] It should be noted that both sodium dodecyl sulfate and sodium hexadec-9-enoate are surfactants. In aqueous solution, they spontaneously form spherical colloidal structures due to the presence of hydrophilic and hydrophobic ends. Two templates are selected here because the colloidal sphere structures formed by different carbon chain lengths are of different sizes, which can be dispersed more evenly here, thereby forming a spherical colloidal soft template of uniform size.
[0074] E. The specific surface area of the carbon nanotubes is ≥700 cm 2 / g;
[0075] The density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ;
[0076] Optionally, the specific surface area of the carbon nanotubes can be 700 cm 2 / g、800cm 2 / g、900cm 2 / g、1000cm 2 / g、1500cm 2 / g、2000cm 2 / g or ≥700cm 2 / g, the density at 25°C can be 1.7 g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 or 1.7g / cm 3 -1.9g / cm 3 Any value between
[0077] In some embodiments, the carbon nanotubes are single-walled carbon nanotubes;
[0078] F. The endpoint of the second mixing is that the solution B forms a Tyndall effect.
[0079] It should be noted that the reason for the Tyndall effect is that when the concentration of the substance in the solution reaches a certain value, a colloidal structure will be generated. When the colloid concentration reaches a certain value, the Tyndall effect will occur. Therefore, whether the solution B forms the Tyndall effect can be used to determine whether the soft template is formed.
[0080] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0081] A. The mass ratio of the organic acid, the organic amine and the water is 0.4832-1:0.2885-1:100-200;
[0082] Optionally, the mass ratio of the organic acid, the organic amine and the water may be 0.4832:0.2885:100, 0.5:0.2885:100, 0.7:0.2885:100, 1:0.2885:100, 0.4832:0.2885:150, 0.4832:0.2885:200, 0.4832:0.5:100, 0.4832:1:100, 1:1:200 or any value between 0.4832-1:0.2885-1:100-200;
[0083] B. The mass ratio of the sodium alkyl sulfonate, the sodium alkyl olefinate, and the water is 0.054-1:0.022-1:60-100;
[0084] Optionally, the mass ratio of sodium alkyl sulfonate, sodium alkyl olefinate, and water may be 0.054:0.022:60, 0.1:0.022:60, 0.5:0.022:60, 1:0.022:60, 0.054:0.1:60, 0.054:0.5:60, 0.054:1:60, 0.054:0.022:80, 0.054:0.022:100, 1:1:100, or any value between 0.054-1:0.022-1:60-100;
[0085] C. The mass ratio of the solution A to the solution B is 1.677-2:1-2;
[0086] Optionally, the mass ratio of solution A to solution B may be 1.677:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 1.677:2, 2:2 or any value between 1.677-2:1-2;
[0087] D. The liquid-to-solid ratio of the solution C and the carbon nanotubes is 1L-2L:1.677g-2g.
[0088] Optionally, the liquid-to-solid ratio of solution C to carbon nanotubes may be 1L:1.677g, 2L:1.677g, 1L:1.7g, 1L:1.8g, 1L:2g, 2L:2g or any value between 1L-2L:1.677g-2g.
[0089] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0090] A. before the hydrothermal reaction, the solution D and ethanol are mixed for the fifth time and ultrasonicated;
[0091] It should be noted that the addition of ethanol during ultrasound can make the spherical colloidal soft template and carbon nanotubes disperse more evenly, so that when forming a series of spherical structures, they will also be more uniform;
[0092] B. The temperature of the hydrothermal reaction is 160°C-240°C, and the time is 6h-8h;
[0093] Optionally, the temperature of the hydrothermal reaction may be 160°C, 180°C, 200°C, 220°C, 240°C or any value between 160°C and 240°C, and the time may be 6h, 7h, 8h or any value between 6h and 8h;
[0094] C. The protective gas in the protective atmosphere includes one or more of argon and nitrogen;
[0095] D. The calcination temperature is 1000°C-1400°C, the time is 2h-15h, and the heating rate is 5°C / min-10°C / min;
[0096] Optionally, the calcination temperature may be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or any value between 1000°C and 1400°C, the calcination time may be 2h, 5h, 10h, 15h or any value between 2h and 15h, and the heating rate may be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5°C / min and 10°C / min;
[0097] It should be noted that some organic matter that is not decomposed during the calcination process will be completely decomposed, and the decomposition of functional groups in the raw materials such as hydroxyl and carboxyl will produce a void structure, thereby forming pore structures of varying sizes. In addition, at temperatures in the range of 1000°C-1400°C, more closed-pore structures will be formed, which is crucial for the electrochemical stability of the negative electrode material of the sodium ion battery.
[0098] E. The stirring rate of the first mixing is 600r / min-800r / min, and the time is 2h-4h;
[0099] Optionally, the stirring rate of the first mixing can be 600r / min, 700r / min, 800r / min or any value between 600r / min-800r / min, and the time can be 2h, 3h, 4h or any value between 2h-4h;
[0100] F. The stirring rate of the second mixing is 600r / min-800r / min, and the time is 2h-4h;
[0101] Optionally, the stirring rate of the second mixing may be 600 r / min, 700 r / min, 800 r / min or any value between 600 r / min-800 r / min, and the time may be 2 h, 3 h, 4 h or any value between 2 h-4 h;
[0102] G. The third mixing comprises: adding the solution A dropwise into the solution B;
[0103] H. The stirring rate of the fourth mixing is 600r / min-800r / min, and the time is 2h-4h.
[0104] Optionally, the stirring rate of the fourth mixing can be 600 r / min, 700 r / min, 800 r / min or any value between 600 r / min-800 r / min, and the time can be 2 h, 3 h, 4 h or any value between 2 h and 4 h.
[0105] In some embodiments, the method for preparing the negative electrode material for a sodium ion battery satisfies at least one of the following conditions:
[0106] A. The mass ratio of the solution D to the ethanol is 212.5-425:1-2;
[0107] Optionally, the mass ratio of solution D to ethanol can be 212.5:1, 300:1, 400:1, 425:1, 212.5:2, 425:2 or any value between 212.5-425:1-2;
[0108] B. The ultrasonic time is 1h-2h.
[0109] Optionally, the ultrasonication time can be 1 h, 1.5 h, 2 h or any value between 1 h and 2 h.
[0110] A second aspect of the present application provides a sodium ion battery negative electrode material, which is prepared by the preparation method of the sodium ion battery negative electrode material.
[0111] A third aspect of the present application provides a sodium ion battery, comprising the sodium ion battery negative electrode material and an electrolyte.
[0112] In some embodiments, the method for preparing the electrolyte comprises:
[0113] Dimethyl ether, sodium trifluoromethanesulfonate and sodium methyl mercaptan are mixed.
[0114] It should be noted that the use of sodium methyl mercaptan as an electrolyte additive reduces the solvation energy of the electrolyte, enhances the transmission efficiency of sodium ions, and enhances the reversibility during rapid charge and discharge, thereby enhancing its cycle life; sodium methyl mercaptan contributes to the formation of the SEI film of the material and the sodium replenishment effect when it initially contacts the electrolyte. This is because sodium methyl mercaptan will completely dissolve in organic solvents, thereby producing a solvation effect, and will move with the movement of the electrolyte. During charge and discharge, part of the electrolyte will decompose, and when it contacts the hard carbon surface, it will be preserved around the material due to weak adsorption (hydrogen bonding) to form an SEI layer. Sodium methyl mercaptan will carry sodium ions, so it can play a role in sodium replenishment. When the electrolyte contacts the material, the weak diffusion effect will cause the material to undergo a simple pre-sodiumization; the coulombic efficiency of the first cycle of the material can be improved, and the prepared electrolyte can reduce the solvation energy, which is beneficial to the embedding and removal of the material.
[0115] In some embodiments, the mass ratio of the ethanol dimethyl ether, the sodium trifluoromethanesulfonate, and the sodium methyl mercaptan is 90-100:17.206-20:0.1-0.2.
[0116] Optionally, the mass ratio of dimethyl ether, sodium trifluoromethanesulfonate and sodium methyl mercaptan can be 90:17.206:0.1, 95:17.206:0.1, 100:17.206:0.1, 90:18:0.1, 90:19:0.1, 90:20:0.1, 90:17.206:0.2, 100:20:0.2 or any value between 90-100:17.206-20:0.1-0.2.
[0117] A fourth aspect of the present application provides an electrical device, including the sodium ion battery.
[0118] It should be noted that electrical equipment includes but is not limited to one or more of electric vehicles, electric bicycles, smart home devices, robots, heavy trucks, ships and energy storage systems.
[0119] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0120] Example 1
[0121] A first aspect of this embodiment provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0122] S1: 2.5 mmol of citric acid and 2 mmol of octamethylenediamine were mixed and dissolved in 100 mL of deionized water to form solution A, and the stirring rate was 600 r / min;
[0123] S2: 0.2 mmol sodium dodecyl sulfate and 0.08 mmol sodium hexadec-9-enoate were dissolved in 60 mL of deionized water to form solution B, and the solution was stirred until the Tyndall effect was observed in solution B when irradiated with a laser lamp;
[0124] S3: gradually add solution A dropwise into solution B, and stir until the solution turns slightly light blue to obtain solution C;
[0125] S4: 0.1 g of carbon nanotubes (single-walled carbon nanotubes with a specific surface area of ≥700 cm 2 / g, and the density at 25°C is 1.7 g / cm 3 -1.9g / cm3 ) was added to solution C, and stirred at a speed of 800 r / min for 2 h to form solution D. Solution D was added with 10 mL of ethanol solution and placed in an ultrasonic device for ultrasonication for 1 h;
[0126] S5: Solution D was transferred to a 200 mL reactor, subjected to hydrothermal reaction at 200 °C for 6 h, and centrifuged at 16000 r / min to obtain a carbon ball-carbon nanotube composite precursor; the solution was calcined at 1300 °C in an argon atmosphere for 2 h with a heating rate of 5 °C / min to obtain the sodium ion battery negative electrode material HCS-1300.
[0127] A second aspect of this embodiment provides a sodium ion battery negative electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material.
[0128] The SEM of the negative electrode material of the sodium ion battery is shown in Figure 1 shown.
[0129] A third aspect of the present embodiment provides a sodium ion battery, comprising a negative electrode sheet prepared from the above-mentioned sodium ion battery negative electrode material and an electrolyte, wherein the preparation method of the negative electrode sheet comprises:
[0130] The above-mentioned sodium ion battery negative electrode material, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, and the slurry was applied on a copper foil current collector after stirring for 4 hours. After vacuum drying, a small round negative electrode sheet with a diameter of 16 mm was obtained;
[0131] The preparation method of the sodium ion battery comprises: preparing a button-type battery in the order of a negative electrode shell, a spring sheet, a gasket, a sodium sheet, a glass fiber separator, an electrolyte, a negative electrode sheet, and a positive electrode shell.
[0132] The preparation method of the electrolyte comprises: adding 0.1 mol of sodium trifluoromethanesulfonate and 0.1 g of sodium methyl mercaptan into 100 mL of dimethyl ether, stirring until all are dissolved and the solution is light yellow, ultrasonicating for 30 minutes, and obtaining the electrolyte after full and uniform dissolution.
[0133] The electrochemical performance of the sodium ion battery at a current density of 20C (1C = 1000 mAh / g) is as follows Figure 2 shown.
[0134] Example 2
[0135] A first aspect of this embodiment provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0136] S1: 2.5 mmol of citric acid and 2 mmol of octamethylenediamine were mixed and dissolved in 100 mL of deionized water to form solution A, and the stirring rate was 600 r / min;
[0137] S2: 0.2 mmol sodium dodecyl sulfate and 0.08 mmol sodium hexadec-9-enoate were dissolved in 60 mL of deionized water to form solution B, and the solution was stirred until the Tyndall effect was observed in solution B when irradiated with a laser lamp;
[0138] S3: gradually add solution A dropwise into solution B, and stir until the solution turns slightly light blue to obtain solution C;
[0139] S4: 0.1 g of carbon nanotubes (single-walled carbon nanotubes with a specific surface area of ≥700 cm 2 / g, and the density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ) was added to solution C, and stirred at a speed of 800 r / min for 2 h to form solution D. Solution D was added with 10 mL of ethanol solution and placed in an ultrasonic device for ultrasonication for 1 h;
[0140] S5: Solution D was transferred to a 200 mL reactor, subjected to hydrothermal reaction at 200 °C for 6 h, and centrifuged at 16000 r / min to obtain a carbon ball-carbon nanotube composite precursor; the solution was calcined at 1200 °C in an argon atmosphere for 3 h with a heating rate of 5 °C / min to obtain the sodium ion battery negative electrode material HCS-1200.
[0141] A second aspect of this embodiment provides a sodium ion battery negative electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material.
[0142] A third aspect of the present embodiment provides a sodium ion battery, comprising a negative electrode sheet prepared from the above-mentioned sodium ion battery negative electrode material and an electrolyte, wherein the preparation method of the negative electrode sheet comprises:
[0143] The above-mentioned sodium ion battery negative electrode material, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, and the slurry was applied on a copper foil current collector after stirring for 4 hours. After vacuum drying, a small round negative electrode sheet with a diameter of 16 mm was obtained;
[0144] The preparation method of the sodium ion battery comprises: preparing a button-type battery in the order of a negative electrode shell, a spring sheet, a gasket, a sodium sheet, a glass fiber separator, an electrolyte, a negative electrode sheet, and a positive electrode shell.
[0145] The preparation method of the electrolyte comprises: adding 0.1 mol of sodium trifluoromethanesulfonate and 0.1 g of sodium methyl mercaptan into 100 mL of dimethyl ether, stirring until all are dissolved and the solution is light yellow, ultrasonicating for 30 minutes, and obtaining the electrolyte after full and uniform dissolution.
[0146] Example 3
[0147] A first aspect of this embodiment provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0148] S1: 2.5 mmol of citric acid and 2 mmol of octamethylenediamine were mixed and dissolved in 100 mL of deionized water to form solution A, and the stirring rate was 600 r / min;
[0149] S2: 0.2 mmol sodium dodecyl sulfate and 0.08 mmol sodium hexadec-9-enoate were dissolved in 60 mL of deionized water to form solution B, and the solution was stirred until the Tyndall effect was observed in solution B when irradiated with a laser lamp;
[0150] S3: gradually add solution A dropwise into solution B, and stir until the solution turns slightly light blue to obtain solution C;
[0151] S4: 0.1 g of carbon nanotubes (single-walled carbon nanotubes with a specific surface area of ≥700 cm 2 / g, and the density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ) was added to solution C, and stirred at a speed of 800 r / min for 2 h to form solution D. Solution D was added with 10 mL of ethanol solution and placed in an ultrasonic device for ultrasonication for 1 h;
[0152] S5: Solution D was transferred to a 200 mL reactor, subjected to hydrothermal reaction at 200 °C for 6 h, and centrifuged at 16000 r / min to obtain a carbon ball-carbon nanotube composite precursor; the solution was calcined at 1100 °C in an argon atmosphere for 5 h with a heating rate of 5 °C / min to obtain the sodium ion battery negative electrode material HCS-1100.
[0153] A second aspect of this embodiment provides a sodium ion battery negative electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material.
[0154] A third aspect of the present embodiment provides a sodium ion battery, comprising a negative electrode sheet prepared from the above-mentioned sodium ion battery negative electrode material and an electrolyte, wherein the preparation method of the negative electrode sheet comprises:
[0155] The above-mentioned sodium ion battery negative electrode material, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, and the slurry was applied on a copper foil current collector after stirring for 4 hours. After vacuum drying, a small round negative electrode sheet with a diameter of 16 mm was obtained;
[0156] The preparation method of the sodium ion battery comprises: preparing a button-type battery in the order of a negative electrode shell, a spring sheet, a gasket, a sodium sheet, a glass fiber separator, an electrolyte, a negative electrode sheet, and a positive electrode shell.
[0157] The preparation method of the electrolyte comprises: adding 0.1 mol of sodium trifluoromethanesulfonate and 0.1 g of sodium methyl mercaptan into 100 mL of dimethyl ether, stirring until all are dissolved and the solution is light yellow, ultrasonicating for 30 minutes, and obtaining the electrolyte after full and uniform dissolution.
[0158] Example 4
[0159] A first aspect of this embodiment provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0160] S1: 2.5 mmol of citric acid and 2 mmol of octamethylenediamine were mixed and dissolved in 100 mL of deionized water to form solution A, and the stirring rate was 600 r / min;
[0161] S2: 0.2 mmol sodium dodecyl sulfate and 0.08 mmol sodium hexadec-9-enoate were dissolved in 60 mL of deionized water to form solution B, and the solution was stirred until the Tyndall effect was observed in solution B when irradiated with a laser lamp;
[0162] S3: gradually add solution A dropwise into solution B, and stir until the solution turns slightly light blue to obtain solution C;
[0163] S4: 0.1 g of carbon nanotubes (single-walled carbon nanotubes with a specific surface area of ≥700 cm 2 / g, and the density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ) was added to solution C, and stirred at a speed of 800 r / min for 2 h to form solution D. Solution D was added with 10 mL of ethanol solution and placed in an ultrasonic device for ultrasonication for 1 h;
[0164] S5: Solution D was transferred to a 200 mL reactor, subjected to hydrothermal reaction at 200 °C for 6 h, and centrifuged at 16000 r / min to obtain a carbon ball-carbon nanotube composite precursor; the solution was calcined at 1000 °C in an argon atmosphere for 8 h with a heating rate of 5 °C / min to obtain the sodium ion battery negative electrode material HCS-1000.
[0165] A second aspect of this embodiment provides a sodium ion battery negative electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material.
[0166] A third aspect of the present embodiment provides a sodium ion battery, comprising a negative electrode sheet prepared from the above-mentioned sodium ion battery negative electrode material and an electrolyte, wherein the preparation method of the negative electrode sheet comprises:
[0167] The above-mentioned sodium ion battery negative electrode material, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, and the slurry was applied on a copper foil current collector after stirring for 4 hours. After vacuum drying, a small round negative electrode sheet with a diameter of 16 mm was obtained;
[0168] The preparation method of the sodium ion battery comprises: preparing a button-type battery in the order of a negative electrode shell, a spring sheet, a gasket, a sodium sheet, a glass fiber separator, an electrolyte, a negative electrode sheet, and a positive electrode shell.
[0169] The preparation method of the electrolyte comprises: adding 0.1 mol of sodium trifluoromethanesulfonate and 0.1 g of sodium methyl mercaptan into 100 mL of dimethyl ether, stirring until all are dissolved and the solution is light yellow, ultrasonicating for 30 minutes, and obtaining the electrolyte after full and uniform dissolution.
[0170] Example 5
[0171] A first aspect of this embodiment provides a method for preparing a negative electrode material for a sodium ion battery, comprising:
[0172] S1: 2.5 mmol of citric acid and 2 mmol of octamethylenediamine were mixed and dissolved in 100 mL of deionized water to form solution A, and the stirring rate was 600 r / min;
[0173] S2: 0.2 mmol sodium dodecyl sulfate and 0.08 mmol sodium hexadec-9-enoate were dissolved in 60 mL of deionized water to form solution B, and the solution was stirred until the Tyndall effect was observed in solution B when irradiated with a laser lamp;
[0174] S3: gradually add solution A dropwise into solution B, and stir until the solution turns slightly light blue to obtain solution C;
[0175] S4: 0.1 g of carbon nanotubes (single-walled carbon nanotubes with a specific surface area of ≥700 cm 2 / g, and the density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ) was added to solution C, and stirred at a speed of 800 r / min for 2 h to form solution D. Solution D was added with 10 mL of ethanol solution and placed in an ultrasonic device for ultrasonication for 1 h;
[0176] S5: Solution D was transferred to a 200 mL reactor, subjected to hydrothermal reaction at 200 °C for 6 h, and centrifuged at 16000 r / min to obtain a carbon ball-carbon nanotube composite precursor; the solution was calcined at 1400 °C in an argon atmosphere for 10 h with a heating rate of 5 °C / min to obtain the sodium ion battery negative electrode material HCS-1400.
[0177] A second aspect of this embodiment provides a sodium ion battery negative electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material.
[0178] A third aspect of the present embodiment provides a sodium ion battery, comprising a negative electrode sheet prepared from the above-mentioned sodium ion battery negative electrode material and an electrolyte, wherein the preparation method of the negative electrode sheet comprises:
[0179] The above-mentioned sodium ion battery negative electrode material, conductive carbon black and PVDF were prepared into a slurry in a mass ratio of 8:1:1, and the slurry was applied on a copper foil current collector after stirring for 4 hours. After vacuum drying, a small round negative electrode sheet with a diameter of 16 mm was obtained;
[0180] The preparation method of the sodium ion battery comprises: preparing a button-type battery in the order of a negative electrode shell, a spring sheet, a gasket, a sodium sheet, a glass fiber separator, an electrolyte, a negative electrode sheet, and a positive electrode shell.
[0181] The preparation method of the electrolyte comprises: adding 0.1 mol of sodium trifluoromethanesulfonate and 0.1 g of sodium methyl mercaptan into 100 mL of dimethyl ether, stirring until all are dissolved and the solution is light yellow, ultrasonicating for 30 minutes, and obtaining the electrolyte after full and uniform dissolution.
[0182] Comparative Example 1
[0183] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that sodium methyl mercaptan is not added to the electrolyte of this comparative example, and other conditions are consistent with Example 1.
[0184] Comparative Example 2
[0185] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example does not use octamethylenediamine, and other conditions are consistent with Example 1.
[0186] Comparative Example 3
[0187] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that carbon nanotubes are not added in this comparative example, and other conditions are consistent with Example 1.
[0188] Comparative Example 4
[0189] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example does not use sodium dodecyl sulfate, and other conditions are consistent with Example 1.
[0190] Comparative Example 5
[0191] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example does not use sodium hexadec-9-enoate, and other conditions are consistent with Example 1.
[0192] Comparative Example 6
[0193] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example does not use citric acid, and other conditions are consistent with Example 1.
[0194] Comparative Example 7
[0195] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that this comparative example does not perform a hydrothermal reaction, and other conditions are consistent with Example 1.
[0196] Comparative Example 8
[0197] This comparative example provides a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. The difference from Example 1 is that the calcination temperature of this comparative example is 1500° C., and other conditions are consistent with Example 1.
[0198] The sodium ion batteries prepared in the above examples and comparative examples were subjected to electrochemical performance tests, and the specific test results are shown in Table 1.
[0199] Table 1 Electrochemical performance test
[0200]
[0201]
[0202] The sodium ion batteries prepared in the above examples and comparative examples were tested for spherical particle size, BET porosity, and D50. The specific test results are shown in Table 2.
[0203] Table 2 Spherical particle size, BET porosity, D50 test
[0204] Material Characteristic spherical particle size (nm) <![CDATA[Porosity (mg / cm 3 )]]> D50(μm) Example 1 40-60 303.6 40-50 Example 2 40-60 287.8 40-50 Example 3 40-60 296.5 40-50 Example 4 40-60 277.5 40-50 Example 5 40-60 289.3 40-50 Comparative Example 1 80-100 200.1 70-80 Comparative Example 2 100-120 189.6 70-80 Comparative Example 3 40-60 289.6 40-50 Comparative Example 4 50-70 170.89 70-80 Comparative Example 5 50-70 168.16 70-80 Comparative Example 6 / 65.12 140-150 Comparative Example 7 / 68.12 140-150 Comparative Example 8 40-60 287.12 70-80
[0205] From the above experiments, it can be seen that the two soft templates have a regulating effect on the spherical particle size of the material. When used at the same time, the spherical particle size is 40-60nm, and the spherical particle size changes after the change. In addition, the acidic environment provided by citric acid is necessary. When citric acid is not used, a normal spherical structure cannot be produced; in addition, high temperature and high pressure conditions of hydrothermal treatment are also necessary. Without hydrothermal treatment, a normal spherical structure cannot be produced; the calcination temperature will affect the pore structure of the material surface, and then affect the initial charge and discharge efficiency of the material and the stability of the material; the amount of sodium methyl mercaptan affects the solvation effect of the electrolyte. Only sodium methyl mercaptan at a suitable concentration can form an effective SEI layer and increase its rate performance.
[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0207] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: include: The organic acid, the organic amine and water are first mixed to obtain a solution A; Sodium alkyl sulfonate, sodium alkyl olefinate and water are mixed for the second time to obtain solution B; The solution A and the solution B are mixed for the third time to obtain a solution C; The solution C and the carbon nanotubes are mixed for the fourth time to obtain a solution D; The solution D is subjected to hydrothermal reaction and solid-liquid separation to obtain a composite precursor; The composite precursor is calcined under a protective atmosphere to obtain a negative electrode material for a sodium ion battery.
2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. the organic acid comprises citric acid; B. the organic amine includes 1,8-diaminooctane; C. the sodium alkyl sulfonate includes sodium dodecyl sulfonate; D. the alkyl olefin sodium includes sodium hexadecene-9-olefin; E. The specific surface area of the carbon nanotubes is ≥700 cm 2 / g; The density at 25°C is 1.7 g / cm 3 -1.9g / cm 3 ; F. The endpoint of the second mixing is that the solution B forms a Tyndall effect.
3. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. The mass ratio of the organic acid, the organic amine and the water is 0.4832-1: 0.2885-1:100-200; B. The mass ratio of the sodium alkyl sulfonate, the sodium alkyl olefinate, and the water is 0.054-1:0.022-1:60-100; C. The mass ratio of the solution A to the solution B is 1.677-2:1-2; D. The liquid-to-solid ratio of the solution C and the carbon nanotubes is 1L-2L:1.677g-2g.
4. The method for preparing a negative electrode material for a sodium ion battery according to any one of claims 1 to 3, characterized in that: At least one of the following conditions is met: A. before the hydrothermal reaction, the solution D and ethanol are mixed for the fifth time and ultrasonicated; B. The temperature of the hydrothermal reaction is 160°C-240°C, and the time is 6h-8h; C. The protective gas in the protective atmosphere includes one or more of argon, argon and nitrogen; D. The calcination temperature is 1000°C-1400°C, the time is 2h-15h, and the heating rate is 5°C / min-10°C / min; E. The stirring rate of the first mixing is 600r / min-800r / min, and the time is 2h-4h; F. The stirring rate of the second mixing is 600r / min-800r / min, and the time is 2h-4h; G. The third mixing comprises: adding the solution A dropwise into the solution B; H. The stirring rate of the fourth mixing is 600r / min-800r / min, and the time is 2h-4h.
5. The method for preparing a negative electrode material for a sodium ion battery according to claim 4, characterized in that: At least one of the following conditions is met: A. The mass ratio of the solution D to the ethanol is 212.5-425:1-2; B. The ultrasonic time is 1h-2h.
6. A negative electrode material for a sodium ion battery, characterized in that: The negative electrode material for a sodium ion battery is prepared by the method for preparing the negative electrode material for a sodium ion battery according to any one of claims 1 to 5.
7. A sodium ion battery, characterized in that: It comprises the sodium ion battery negative electrode material and electrolyte as described in claim 6.
8. The sodium ion battery according to claim 7, characterized in that: The preparation method of the electrolyte comprises: Dimethyl ether, sodium trifluoromethanesulfonate and sodium methyl mercaptan are mixed.
9. The sodium ion battery according to claim 8, characterized in that: The mass ratio of the ethanol dimethyl ether, the sodium trifluoromethanesulfonate and the sodium methyl mercaptan is 90-100:17.206-20:0.1-0.
2.
10. An electrical equipment, characterized in that: A sodium ion battery comprising the sodium ion battery of any one of claims 7 to 9.